Pre-Wedding Processes in Mandailing Traditional Perfective Uruf (Case Study of Padang Lawas Regency) - Husnul Hayana Daulay (Jurnal Penelitian Agama, 2022)
Every Marriage in the Mandailing custom is not only an inner birth bond between a man and a woman but there is a customary bond that has values that must be adhered to. Marriage, in the sense of customary engagement, is a marriage that has legal consequences for customary law, which applies in the society in question. The result of this law occurs, for example, in the presence of application relationships that are the taste of relatives (child relations, bachelors of daughters) and rasah tuha (relationships between the family of the future husband and wife). Marriage in mandailing custom is something very sacred, every procession or practice in marriage is attached to traditional values, be it premarital processions such as mangaririt boru, padamos hata, patobang hata, and senior sere. Post-marriage processions such as, marulahari, mangupa-upa and so on, all this is inseparable from the customs that are still attached to the Mandailing customs. All the traditional practices of Mandailing are inseparable from the role of dalihan na tolu especially when it comes to marriage. The urf included in the Marriage Procession in the Mandailing custom is 'urf fasid which is a rule that is applicable and recognized by the community but contrary to Islamic law.